RAGAM BAHASA INDONESIA DALAM KOMUNIKASI POLITIK - Sitti Rabiah (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2016)
Indonesian language as the part of the Indonesian struggle for independence through the Sumpah Pemuda in 1928 confirmed the Indonesian language as the national language and unifying language of various races, religions and ethnicities. Post-independence, the Indonesian language strengthen its presence as a "state administration". If viewed from both sides, the Indonesian language has contributed to the development of social, cultural and political activities for the Indonesian nation. After the reform era, the Indonesian language continues to grow. One of the usesin political communication, especially political campaigns. The use of this language is to gain sympathy, attention, and perception of the public to make a choice in the general election. The method used in this study is descriptive method with qualitative approach. Data was collected by literature review. The results showed that the political campaign is the one of the implementation of political communication from the candidates to the public.Performance shown when delivering his message in front of the audience/public needs to be supported with appropriate variety of language and clear message. The variety of Indonesian language in political campaign with open campaign model should be informal language, then the dialogic campaign model should be formal language. Some snippets of campaign text that have been discussed show that the uses of language there still has not been proper use of the word. The application of variety of language is a reflection of the candidatespersonality so that appropriate usage of words also give effect to the audience/voter in determining their choice. The study recommends collaboration among political actors with language experts in creating political communication integrity.